Formal Approach to Integrating Feature and Architecture Models - Janota, Mikoláš; Botterweck, Goetz (Fundamental Approaches to Software Engineering, 2008)
If we model a family of software applications with a feature model and an architecture model, we are describing the same subject from different perspectives. Hence, we are running the risk of inconsistencies. For instance, the feature model might allow feature configurations that are not realizable by the architecture. In this paper we tackle this problem by providing a formalization of dependencies between features and components. Further, we demonstrate that this formalization offers a better understanding of the modeled concepts. Moreover, we propose automated techniques that derive additional information and provide feedback to the user. Finally, we discuss how some of these techniques can be implemented.